Legal Protection of Geographical Indications and the Realization of Community Welfare - Vincentius Patria Setyawan (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Abstract Indonesia has a strategic geographical location, namely located between 2 (two) continents and 2 (two) oceans. The implication of Indonesia's strategic location geographically is that Indonesia has natural riches that are characterized by unique biodiversity, which is not found in any other country in the world. The advantages of Indonesia's natural wealth must be protected, in order to provide benefits, especially for the welfare of society. This article will discuss the protection of geographical indications as part of intellectual property rights to natural resources which should be utilized as much as possible for the welfare of society. This article was written using a type of normative legal research with a conceptual approach. The results of this research are that protection of geographical indications is protection of the economic rights of local communities in order to achieve community welfare. Keywords: legal protection, geographical indications, community welfare.